Talent strategies and leadership development of the public sector : insights from Southeast Asia - Lee, Celia (Abingdon, Oxon ; New York, NY : Routledge, 2021)
To stay ahead of the competition, the public sector has to ensure an effective talent management strategy to attract, develop and retain talents. Effective talent management is about aligning the organisation's approach to talent with the strategic aims and purpose of the organisation. This book adopts a comparative country analysis, which takes into accountthe institutional emphasis, organisational configuration and unique characteristics of the public sector. Against the backdrop of three major stages of administrative development, i.e., the colonial, postcolonial and modern periods, this book unpacks how the talent schemes have been shaped by the reforms, experiences, cross-country knowledge transfers and evolved over time responding to globalisation and digitalisation in Southeast Asia. This book will be of great interest to scholars and public managers working on public administration and civil service reforms in Asia towards developing a contextualised understanding of talent management and leadership development in the region.
"Routledge Focus"--Cover.
OCLC-licensed vendor bibliographic record.
Keywords: Civil service -- Southeast Asia -- Personnel management; Civil service reform -- Southeast Asia; Public officers -- Training of -- Southeast Asia; Leadership -- Southeast Asia; BUSINESS & ECONOMICS / Leadership; POLITICAL SCIENCE / Political Process / Leadership; POLITICAL SCIENCE / Public Affairs & Administration